Efficacy of the Best Possible Self protocol in diabetes self-management: A mixed-methods approach. (March 2021) - Gibson, Ben; Umeh, Kanayo F; Newson, Lisa; Davies, Ian
Recent research has demonstrated that positive affect may facilitate illness self-management. This study used a sequential exploratory mixed-methods typology to assess whether a brief writing task designed to boost positive affect (the Best Possible Self protocol) could improve aspects of diabetes self-management, specifically. A qualitative investigation explored people with diabetes' ( n  = 20) views regarding Best Possible Self feasibility and acceptability, while a subsequent quantitative investigation assigned people with diabetes ( n  = 50) to a Best Possible Self or non-Best Possible Self condition and assessed affect and self-management behaviours over a 4-week period. Findings indicated that individuals were receptive to the Best Possible Self and that it provided benefits for diabetes self-management.